MODERN METHODOLOGICAL APPROACHES TO ASSESSING THE INVESTMENT ATTRACTIVENESS OF INDUSTRIAL ENTERPRISES - YEPIFANOVA, IRYNA; DZHEDZHULA, VIACHESLAV; KOVAL, KATERINA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article summarizes the existing methodological approaches to assessing the level of investment attractiveness of industrial enterprises.The main methodological approaches to assessing the state of investment attractiveness management are studied. It was found that the most used methods of assessing investment attractiveness are: the method of expert assessments; rating method; integrated assessment of investment attractiveness; method of comparisons; matrix method; profitability triangle; differentiated approach; methods that are based on the use of artificial intelligence. The advantages and disadvantages of each of the methods are analyzed.The matrix approach to the assessment of the level of investment attractiveness of the researched enterprise has been further developed. Given the current state of domestic industrial enterprises, in the matrix method of assessing investment attractiveness in the matrix of quantitative indicators (liquidity, financial stability, return on capital, property indicators) indicators of business activity are replaced by indicators of bankruptcy probability. This is due to the fact that both indicators of business activity and profitability indicators characterize the efficiency of the enterprise. The absence of signs of bankruptcy will allow the investor to better assess the investment attractiveness of the enterprise. Indicators that should be included in the matrix include depreciation rate, renewal rate, asset mobility ratio, coverage ratio, quick liquidity ratio, absolute liquidity ratio, autonomy ratio, equity maneuverability ratio, financial risk ratio; return on assets; return on equity; profitability ratio of operating activities; beaver ratio, financial leverage ratio, asset coverage ratio with net working capital.
Keywords: investment attractiveness; matrix method; integrated assessment; profitability triangle